Efek Penggunaan Maksimum dan Minimum Heat Input di Perbaikan Pipa Menggunakan Metode Weld-Deposition Guna Menghidari Terjadinya Burn-Through dan Hydrogen Cracking - Wira Anom Wibawa; M. N. Ilman (Institut Teknologi Adhi Tama Surabaya, 2022)
Decreasing quality of the pipes damage might influence the business process exploration, production, distribution, and buying and selling of oil and natural gas of a company. One of common method is known cheap and being effectively applied to improve the pipes construction; it is known as weld-deposition. Pipe repair using the weld-deposition method is inseparable from the risk of failure that may occur, namely burn-through and hydrogen cracking. In this study, welding was carried out on API 5L grade B pipes with a diameter of 4 inches and a pipe thickness of 4 mm. Welding is done with a pipe in which there is a flow of water with a flow volume of 5 lpm. The welding parameters used are welding current ranging from 120 A, voltage to 20V, and speed varying from 10 mm/s to 0.5 mm/s which produces heat input ranging from 0.192 kJ/mm to 3.84 kJ/mm. Investigation confirms a mocrostructure and hardness level. This study resulted in recommendations for welding parameters that need to be avoided in order to avoid burn-through and the risk of hydrogen cracking. In this study, there was no burn-through even though the welding was carried out with a high heat input of 3.84 kJ/mm and the minimum heat input was limited to 0.32 kJ/mm so as not to have the potential for hydrogen cracking to occur.Kata kunci: API 5L grade B, weld-deposition, burn-through, hydrogen crack, heat input.